Telepsychiatry in Oman within the broader framework of telehealth - Tamadhir Al-Mahrouqi; Alya Al Harrasi; Fatma Al Rajhi; Hamed Al Sinawi; Mohammed Al-Alawi (BJPsych International)
In recent years, the Sultanate of Oman has made strides in telehealth services to improve healthcare access for underserved patients, specifically through telephone consultations and digital appointment scheduling. However, the lack of technological infrastructure, insufficient training for healthcare providers and the absence of a unified digital system limit its full potential. As a result, patients in remote areas experience delays in diagnosis and treatment.